Atypical Progeroid Syndrome with Familial Partial Lipodystrophy due to A Missense c.1045 C > T LMNA Mutation: A Case Report and an Innovative Therapeutic Approach - Russo, Benedetta; Menduni, Marika; Mari, Andrea; Pelosini, Caterina; Brancati, Francesco; D’Apice, Maria Rosaria; Picconi, Fabiana; Frontoni, Simona (Archives of Clinical and Medical Case Reports, 2022)
Familial partial lipodystrophy (FPLD) associated with LMNA gene mutations is a rare form of lipodystrophy disorder characterized by partial absence of subcutaneous adipose tissue and metabolic complications. Recently, this peculiar phenotype has been associated to cardiac disease or to atypical progeroid syndrome (APS). We present a case of 31-yearold woman with progeria features, partial lipodystrophy, type 2 diabetes mellitus (T2D), hypertriglyceridemia and hepatic steatosis. Genetic analysis revealed a missense heterozygous LMNA mutation c.1045 C > T, p. (Arg349Trp) that established APS diagnosis with FPLD, so far studied and described in only 10 patients worldwide. The patient was initially treated with metformin, fenofibrate, omega-3 and low carb and low fat diet; later, liraglutide (a Glucagon-Like Peptide-1 analog, GLP-1) therapy was added and follow-up was arranged. During the initial follow-up we observed a significant improvement in metabolic and anthropometric conditions, body composition, liver volume and distribution of fat mass with a reduction of visceral fat. However, with disease progression, the patient’s lipid profile worsened, and focal segmental glomerulosclerosis (FSGS) and peripheral neuropathy developed. This case highlights the clinical signs and the progression of this rare lipodystrophy disorder and propose an innovative therapeutic approach to manage the disease.